2020
DOI: 10.1016/j.labeco.2020.101886
|View full text |Cite
|
Sign up to set email alerts
|

Concentration in US labor markets: Evidence from online vacancy data

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 46 publications
6
51
0
Order By: Relevance
“…Scholars have called attention to the multiple pathways along which the pandemic has deepened existing inequalities ( Alon et al 2020 ; Coughlin et al 2020 ; Davis, Hansen, and Seminario-Amez 2020 ; Gourinchas et al 2020 ; Wrigley-Field 2020 ). Our results build on these findings by highlighting how the pandemic may have entrenched prior trends regarding market concentration ( Azar et al 2020 ; Gutiérrez and Philippon 2019 ), particularly in industries with high remotability. As more small businesses fail or cut back their workforces, one would expect an even more hostile environment when the pandemic is contained.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Scholars have called attention to the multiple pathways along which the pandemic has deepened existing inequalities ( Alon et al 2020 ; Coughlin et al 2020 ; Davis, Hansen, and Seminario-Amez 2020 ; Gourinchas et al 2020 ; Wrigley-Field 2020 ). Our results build on these findings by highlighting how the pandemic may have entrenched prior trends regarding market concentration ( Azar et al 2020 ; Gutiérrez and Philippon 2019 ), particularly in industries with high remotability. As more small businesses fail or cut back their workforces, one would expect an even more hostile environment when the pandemic is contained.…”
Section: Discussionsupporting
confidence: 65%
“…In the meantime, other studies have shown a clear monopsony power of firms in the labor market: workers have few options when deciding where to seek employment (Sokolova and Sorensen 2020). The level of concentration is particularly high in rural areas ( Azar et al 2020 ), and there has been a clear upward trend of concentration in manufacturing ( Benmelech, Bergman, and Kim 2018 ). Together, these findings suggest not only that large firms earn greater profits through their high market share but also that the weakened competition for workers discourages these firms from paying higher wages.…”
Section: Between-firm Inequalitymentioning
confidence: 99%
“…In short, there is no well-defined "causal effect of concentration on price," but rather a set of hypotheses that can explain observed correlations of the joint outcomes of price, measured markups, market share, and concentration. 1 As Bresnahan (1989) argued three decades ago, no clear interpretation of the impact of concentration is possible without a clear focus on equilibrium oligopoly demand and "supply," where supply includes the list of the marginal cost functions of the firms and the nature of oligopoly competition.…”
Section: Problems With Some Recent Studies Of Market Powermentioning
confidence: 99%
“…First, we use administrative data to obtain the most comprehensive dataset to date on the labor market concentration of new hires by occupation. Relying on hires is more accurate than relying on job postings (Azar et al, 2017(Azar et al, , 2018(Azar et al, , 2019Hershbein et al, 2018) because not all companies post their jobs online. Data on hires is more accurate for measuring current competition in the labor market than data on the stock of employment, especially when such a stock is based on industries (Benmelech et al, 2018;Rinz, 2018;Lipsius, 2018;Abel et al, 2018) rather than occupations.…”
Section: Introductionmentioning
confidence: 99%